Boiler operator's handbook - Heselton, Kenneth E., 1943- (Fairmont Press ; M. Dekker, 2005)
Containing key information for operators and managers of large and small plants, this is an indispensable guide for those at advanced and early stages of their careers, as well as for managers interested in reducing operating expenses.